Uncover New Reactivity of Genetically Encoded Alkyl Bromide Non-Canonical Amino Acids - Shu, Xin; Asghar, Sana; Yang, Fan; Li, Shang-Tong; Wu, Haifan; Yang, Bing (Frontiers in Chemistry, 2022)
Genetically encoded unnatural amino acids (Uaas) with electrophilic moieties are excellent tools to investigate protein-protein interactions (PPIs) both in vitro and in vivo. These Uaas, including a series of alkyl bromide-based Uaas, mainly target cysteine residues to form protein-protein cross-links. Although some reactivities towards lysine and tyrosine residues have been reported, a comprehensive understanding of their reactivity towards a broad range of nucleophilic amino acids is lacking. Here we used a recently developed OpenUaa search engine to perform an in-depth analysis of mass spec data generated for Thioredoxin and its direct binding proteins cross-linked with an alkyl bromide-based Uaa, BprY. The analysis showed that, besides cysteine residues, BprY also targeted a broad range of nucleophilic amino acids. We validated this broad reactivity of BprY with Affibody/Z protein complex. We then successfully applied BprY to map a binding interface between SUMO2 and SUMO-interacting motifs (SIMs). BprY was further applied to probe SUMO2 interaction partners. We identified 264 SUMO2 binders, including several validated SUMO2 binders and many new binders. Our data demonstrated that BprY can be effectively used to probe protein-protein interfaces even without cysteine residues, which will greatly expand the power of BprY in studying PPIs.